Accounting for Vibration Loads in the Design of Acoustic Reverberation Chamber Structures in the Midas FX Software Package - Dakhi S. Vanus (Железобетонные конструкции)
This article outlines the main provisions in the design of an acoustic reverberation chamber, methods for modeling such objects in engineering and construction practice. A finite element model of an object is presented in the Midas FX software package. As a result of the calculation, it is possible to evaluate the components of the stress-strain state in concrete and in structural elements or on the contact surface, the effect of vibration loads on RAC structures, their interaction with the foundation and soil base, as well as analysis of the use of vibration isolators in the RAC foundation Based on the results of the analysis, recommendations are given for perform calculations of system elements, select design solutions.